PENGEMBANGAN MODEL ANDRAGOGI UNTUK MENINGKATKAN PARTISIPASI JAMAAH MAJELIS TAKLIM NURUL HUDA PUTRI DI DUSUN SEMOYA TEGALTIRTO BERBAH SLEMAN - Endah Yuli Astanti (Millah: Journal of Religious Studies, 2016)
The application of the andragogy principles in the planning, implementation and evaluation of learning help Majelis Taklim members get the most out of learning demonstrated by the increased participation of the congregation as well as the value of cognitive, affective and psychomotor good. Then there was a significant increase in participation of Majelis Taklim member after application of the concept of Andragogy compared with before the implementation of this concept in Majelis Taklim, which is between 70-95%, and the concept of Andragogy more effectively applied to Majelis Taklim the younger participants, such as teenagers or young mothers because this age group had the motivation and interest in learning is higher than older age groups. While the motivation in Andragogy determine the final outcome.